Julia Lathrop - Cohen, Miriam. (Boulder)
1 online resource (212 p.)
Keywords: Julia Lathrop was a social servant, government activist, and social scientist who expanded notions of women's proper roles in public life during the early 1900s. Appointed as chief of the U.S. Children's Bureau, created in 1912 to promote child welfare, she was the first woman to head a United States federal agency. Throughout her life, Lathrop challenged the social norms of the time and became instrumental in shaping Progressive reform. She began her career at Hull House in Chicago, the nation's most famous social settlement, where she worked to improve public and private welfare for poor people, helped establish America's first juvenile court, and pushed for immigrant rights. Lathrop was also co-founder of one of America's first schools of social work. Later in life she became a leader in the League of Women Voters and an advisor on child welfare to the League of Nations. Following Lathrop's life from her childhood and college education through her social service and government work, this book gives an overview of her enduring contribution to progressive politics, women's employment, and women's education. It also offers a look at how one influential woman worked within the bounds of traditional conventions about gender, race, and class, and also pushed against them.